Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00264-013-2048-5
|View full text |Cite
|
Sign up to set email alerts
|

A case of lung metastasis in myxoinflammatory fibroblastic sarcoma: analytical review of one hundred and thirty eight cases

Abstract: Purpose Myxoinflammatory fibroblastic sarcoma (MIFS) is a rare soft tissue tumour first identified at the end of the 1990s. This study presents our experience and literature reviews focusing on risk of recurrence. Methods Rizzoli Orthopaedic Institute database and literature were searched for patients with MIFS observed from 1997 to 2012. Data were analysed in a new database. Results Five patients underwent surgery at our institute, and 133 cases were retrieved from the literature. Not all clinicopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 44 publications
1
50
0
1
Order By: Relevance
“…MIFS is a low‐grade sarcoma with frequent local recurrence if not completely resected . Only very rare cases of lymph node and lung metastasis have been reported . Wide local excision is the treatment of choice if possible to prevent recurrence.…”
Section: Myxoinflammatory Fibroblastic Sarcoma (Inflammatory Myxohyalmentioning
confidence: 99%
“…MIFS is a low‐grade sarcoma with frequent local recurrence if not completely resected . Only very rare cases of lymph node and lung metastasis have been reported . Wide local excision is the treatment of choice if possible to prevent recurrence.…”
Section: Myxoinflammatory Fibroblastic Sarcoma (Inflammatory Myxohyalmentioning
confidence: 99%
“…MIFS most frequently arises as a painless slow-growing tumor in the distal extremities of adults in their 40s with no obvious gender predominance. [1][2][3] The histology of MIFS may be pleomorphic, which makes initial diagnostics challenging. The tumor consists of spindle cells and epithelioid cells with abundant cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 High-grade, metastasizing forms of MIFS are rare, reported to represent some 2% of the cases. 3 Cytogenetic studies on MIFS have revealed a typical reciprocal translocation between chromosomes 1 and 10 t (1:10) (p22; q24), leading to juxtapositioning of parts of the TGFBR3 and MGEEA5 genes. 7,8 No fusion product is formed, however, since the genes are transcribed in opposite directions.…”
Section: Introductionmentioning
confidence: 99%
“…Sakaki et al observed metastasis to a regional lymph node 3 months after resection in one patient and Hassanein et al reported two cases with distant metastases, one to the lung and the other to the skull at 3 months and 5 years, respectively 9 11. Lombardi et al in 2013 reviewed 133 cases from the literature and found four cases presenting with lung metastasis 14. Our case was characterised by an unusual fast progression of tumour presenting as local extension with a soft tissue mass involving the right foot extending to ankle joint viz the tibiotalar and tibiocalcaneal joints as well as metastases to distant bony sites including the vertebrae, rib and lung.…”
Section: Discussionmentioning
confidence: 71%